Transcriptome profiling reveals differential gene expression in proanthocyanidin biosynthesis associated with red/green skin color mutant of pear (Pyrus communis L.) - Yang, Yanan; Yao, Gaifang; Yue, Wenquan; Zhang, Shaoling; Wu, Jun (Frontiers in Plant Science, 2015)
Anthocyanin concentration is the key determinant for red skin color in pear fruit. However, the molecular basis for development of red skin is complicated and has not been well understood thus far. ‘Starkrimson’ (Pyrus communis L.), an introduced red pear cultivated in the north of China and its green mutant provides a desirable red/green pair for identification of candidate genes involved in color variation. Here, we sequenced and annotated the transcriptome for the red /green color mutant at three stages of development using Illumina RNA-seq technology. The total number of mapped reads ranged from 26 to 46 million in six libraries. About 70.11-71.95% of clean reads could be mapped to the reference genome. Compared with green colored fruit, a total of 2,230 differentially expressed genes (DEGs) were identified in red fruit. Gene Ontology (GO) terms were defined for 4,886 differential transcripts involved in 15 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Three DEGs were identified as candidate genes in the flavonoid pathway, LAR, ANR and C3H. Tellingly, higher expression was found for genes encoding ANR and LAR in the green color mutant, promoting the proanthocyanidin (PA) pathway and leading to lower anthocyanin. MYB-binding cis-motifs were identified in the promoter region of LAR and ANR. Based on these findings, we speculate that the regulation of PA biosynthesis might be a key factor for this red/green color mutant. Besides the known MYB and MADS transcription families, two new families, AP2 and WRKY, were identified as having high correlation with anthocyanin biosynthesis in red skinned pear. In addition, qRT-PCR was used to confirm the transcriptome results for 17 DEGs, high correlation of gene expression, further proved that AP2 and WARK regulated the anthocyanin biosynthesis in red skinned ‘Starkrimson’, and ANR and LAR promote PA biosynthesis and contribute to the green skinned variant. This study can serve as a valuable new resource laying a solid foundation for functional gene identification in the anthocyanin pathway of red-skinned pear and provide a good reference for relevant research on molecular mechanisms of color variation in other pear species.